Effects of storage and leukocyte reduction on the concentration and procoagulant activity of extracellular vesicles in canine packed red cells. Issue 2 (10th March 2021) - Avenick, Daniel; Kidd, Linda; Istvan, Stephanie; Dong, Fanglong; Richter, Keith; Edwards, Nicole; Hisada, Yohei; Posma, Jens J.N.; Massih, Cherein Abdel; Mackman, Nigel
Abstract: Objectives: To characterize the size and procoagulant activity of extracellular vesicles (EV) that accumulate in canine packed red blood cells (pRBCs) over time and the effect of leukocyte reduction on these characteristics. Design: Prospective cohort study. Setting: Private small animal specialty referral hospital and university research laboratories. Animals: Ten healthy blood donor dogs. Interventions: Five pRBCs units were obtained according to standard protocols, and 5 were leukocyte‐reduced prior to processing. Platelet‐free supernatant from the pRBC units was collected on days 0, 10, 20, 32, and 42. Measurements and main results: Nanoparticle tracking analysis was performed to determine the size and concentration of EVs. Thrombin generation associated with phosphatidylserine‐positive EVs was determined using a capture assay. Factor Xa generation associated with phosphatidylserine‐positive EVs and tissue factor‐positive EVs was measured in a subset of EVs isolated by centrifugation of the supernatant at 20, 000 × g . R package nparLD and the Mann–Whitney U‐test were used to determine the effect of duration of storage and the effect of leukocyte reduction, respectively. Small (mean < 125 nm) procoagulant EVs accumulated over time, with significant increases occurring on or after day 20 in both non‐leukocyte reduced and leukocyte‐reduced units. The procoagulant activity of the EVs was due to phosphatidylserine, not tissue factor. Increases in EV concentration and procoagulant activity occurred earlier in non‐leukocyte reduced units. Extracellular vesicle accumulation and procoagulant activity were not decreased at any individual time point by leukocyte reduction. Conclusions: Further studies characterizing and determining the clinical relevance of small procoagulant EVs in pRBCs are warranted.